Bandgap Engineering and Tuning of Electronic and Optical Properties of Hetero‑atoms‑doped‑Graphene Composites by Density Functional Quantum Computing for Photocatalytic Applications - Jameel, Muhammad Hasnain; Mayzan, Mohd Zul Hilmi; Roslan, Muhammad Suf; Agam, Mohd Arif; Jabbar, Abdullah Hasan; Badi, Karrar Mahdi; Tuama, Alaa Nihad (Springer, 2024)
Graphene (GR) has considered to be a promising material to build profcient graphene-doped composites photocatalyst with superior catalytic activities for wastewater treatment. During the past decade, diferent graphene-doped composites have been constructed and applied in numerous solar and photocatalyst felds. GR-based composites have a sufcient surface area with numerous photocatalytic sites for wastewater treatment applications. In the present study the efect of hetero-atoms Aluminum, Nitrogen, and Boron on bandgap engineering and tuning of electronic and optical properties of GR-doped-composites by density functional quantum computing calculation. Our computed results demonstrate that heteroatoms-doped-GR composites having direct energy band (Eg) semiconductor nature with an increment from 0.0 to 1.75 eV by the inclusion of hetero-atoms in GR, maybe some extra strong sites are formed in p state into the lifting of the energy bandgap (Eg). An extensive investigation of optical conductivity illustrates that increment in peaks from 2.5 to 4.0. Due to hetero-atoms dopant the absorbance peaks are increased and moved toward higher energy absorption. Our fndings reveal that as compared to pure, Al, N,B hetero-atoms, the B-doped-GR surface has a large surface area with strong active sites for wastewater treatment. These theoretical fndings can be useful in practical applications for wastewater remediation through hetero-atom-doped graphene composites.